Legal and Socio-economic Issues Concerning Black Marketer's Activities of Petroleum Products in Nigeria - Simon Ejokema Imoisi; Paul Atagamen Aidonojie (Universitas Airlangga, 2023)
Petroleum is an essential commodity that is highly demanded by the populace of the world because it is the major and predominant source of energy in the world. Given that there could be an abuse of petroleum products in Nigeria, Section 4 of the Petroleum Act further prohibits the storage and sale of petroleum products by black marketers in Nigerian communities. However, it is unfortunate that due to poor implementation of the Petroleum Act, there has been a constant increase in the activities of black marketers of petroleum products in Nigeria. This study embarks on a hybrid method of studying the activities of black marketers in the Nigerian petroleum industry. In this regard, 322 questionnaires were distributed to respondents residing in Nigeria, and descriptive and analytical methods were adopted to examine the results. The study found that the incidence of black market activities is often caused by legal and socioeconomic challenges, such as poor implementation of the legal framework, petroleum scarcity, poverty, and unemployment. It was therefore concluded that to curtail the activities of black marketers in Nigeria's petroleum industry, there should be a due implementation of the Petroleum Act, provision of petroleum products, and prosecution of persons involved in black market activities in Nigeria's petroleum industry.